2009
DOI: 10.1016/j.molimm.2009.09.003
|View full text |Cite
|
Sign up to set email alerts
|

The chimpanzee Mhc-DRB region revisited: Gene content, polymorphism, pseudogenes, and transcripts

Abstract: In humans, great apes, and different monkey species, the major histocompatibility complex (MHC) class II DRB region is known to display considerable copy number variation. The microsatellite D6S2878 has been shown to be a valuable marker for haplotyping the DR region in humans and macaque species. The present report illustrates that chimpanzee haplotypes also can be discriminated with this marker. The analyses resulted in the description of nine different region configurations, of which seven are present withi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(35 citation statements)
references
References 46 publications
(67 reference statements)
0
31
0
Order By: Relevance
“…Microsatellite typing with D6S2878, which is situated in intron 2 of nearly all DRB genes and possesses STR-length patterns that are haplotype specific, has recently been proven to be an ideal tool for DRB typing in various species (de Groot et al 2008a; de Groot et al 2009; Doxiadis et al 2007a; Doxiadis et al 2009a; Otting et al 2012). Thus, microsatellite typing with this STR has been performed and has resulted in the definition of 22 DRB haplotypes in Indian rhesus macaques (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Microsatellite typing with D6S2878, which is situated in intron 2 of nearly all DRB genes and possesses STR-length patterns that are haplotype specific, has recently been proven to be an ideal tool for DRB typing in various species (de Groot et al 2008a; de Groot et al 2009; Doxiadis et al 2007a; Doxiadis et al 2009a; Otting et al 2012). Thus, microsatellite typing with this STR has been performed and has resulted in the definition of 22 DRB haplotypes in Indian rhesus macaques (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The Mamu - B region can be defined by four different STRs, MIB6, MIB7, MICA and D6S2793, which are situated in the B region of macaques (Bonhomme et al 2008; Doxiadis et al 2009b). The most straightforward genotyping can be performed with microsatellite D6S2878, named DRB-STR, which is localised within intron 2 of virtually all DRB genes and, thus, serves as an excellent tool for haplotyping both macaque and other primate species (de Groot et al 2008a; de Groot et al 2009; Doxiadis et al 2007a; Doxiadis et al 2009a; Otting et al 2012). A combination of all molecular techniques mentioned above has been implemented to screen the Indian and Burmese rhesus macaques and to define their MHC haplotypes.…”
Section: Introductionmentioning
confidence: 99%
“…Both class I and II genes are highly polymorphic, mostly in the regions encoding the peptide groove. Direct investigations of MHC in other species, including pig and primates, reported similar variability in class I and class II genes [36][37][38]. In addition, other aCGH studies have already shown that MHC genes in ruminants are affected by CNV [23,24,26,27].…”
Section: Annotation Of Cnvrsmentioning
confidence: 74%
“…Comparison of the groups deduced from exon 2 and those observed for the STR was not always consistent, just as in previous reports concerning OWM published by Bontrop et al ., [23], [24], [49].…”
Section: Discussionmentioning
confidence: 99%